STRATEGY OF HIGHER EDUCATION THROUGH HARMONY LEADERSHIP (DEVELOPMENT STUDY OF BAKTI INDONESIA UNIVERSITY BANYUWANGI) - haya (International Jurnal of Education Schoolars, 2020)
Higher education in Indonesia has stagnated in terms of academic achievement and benefits for society. This study intends to find new strategies for developing local campuses with national and international academic reputations. The data was obtained through a single case study, namely Bakti Indonesia University Banyuwangi, East Java, Indonesia because it was relevant to the research objectives. Harmony leadership orchestrates potential conflicts with strategies of reconciliation, accessibility, networking, and spirituality so as to achieve a reputation for being effective and productive. The research findings correct Thomas and Kilman's theory of 5 styles of conflict management.